ANALYSIS OF CONTRACEPTIVE USE IN WOMEN OF FERTILE AGE IN LAHAT DISTRICT, SOUTH SUMATERA - Yuniarti, Nini Iswara; Maksuk, Maksuk; Minarti, Minarti (Indonesia Epidemiological Journal, 2025)
Background: One of the efforts to improve maternal health is through contraceptive services. The objective of the study was to analyze the use of contraceptives in the work area of the Lahat Regency Health Center, South Sumatra. Methods: The type of research is an analytical survey research with a cross-sectional design. This research was conducted in the Simpang III Pumu Health Center Working Area, Lahat Regency, South Sumatra, from May to July 2023. The sample was 169 women of childbearing age in the Simpang III Pumu Health Center Working Area, Lahat Regency. The sampling technique was a simple random method. Results: The results of the study showed that as many as 35.5% of women of childbearing age had used contraception, namely the majority in the non-risk age group, working. While factors related to the use of contraception are age group, education level, knowledge, family support, and officers. Conclusion: The dominant factor to determine the use of contraception is family support. It is necessary to conduct a counseling program for every family, especially those who have not yet participated in family planning.